Analysis of Ideology in Prabowo’s Speech at The G20 Summit - Salsa Yasshinta Mustika Dewi; Susylowati, Eka (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
This study analyzes the ideological content of Prabowo Subianto’s speech at the G20 Summit using Norman Fairclough’s Critical Discourse Analysis (CDA) framework. The research aims to explore how Prabowo constructs political narratives around food security and the Gaza conflict to reinforce Indonesia’s domestic and global positioning. The analysis focuses on three CDA dimensions: micro (text), mezzo (discursive practice), and macro (social practice), exploring how language reflects and shapes ideology and power. By examining linguistic features, discursive practices, and broader social contexts, the study reveals how language is employed to legitimize leadership, align national priorities with international values, and advocate for multilateral cooperation. The findings show that Prabowo’s rhetorical strategies effectively merge national interests with global concerns, reflecting Indonesia’s aspirations as a representative of the Global South and a proponent of peace, justice, and sustainable development.